Expandable suspension-type porous polyvinyl chloride resin powder and polyvinyl chloride plastisol composition
By incorporating a thermally decomposable foaming component into porous vinyl chloride resin powder, the method addresses the issue of heavy carpet tiles by creating a lightweight, uniform foamed resin layer with fine cells and adequate strength.
Patent Information
- Application Number
- JP2021052565
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-03-26
AI Technical Summary
The use of inorganic fillers in carpet tile backing layers results in heavy products, and foaming agents often create non-uniform foam cells, compromising appearance and functionality.
Incorporating a thermally decomposable foaming component into the pores of a suspension-based porous vinyl chloride resin powder, which undergoes fine and uniform foaming during heat molding to form a lightweight, uniform foamed resin layer.
The method produces a lightweight, uniform foamed resin layer with fine cells, achieving balanced properties and sufficient strength, suitable for applications like carpet tile backing layers.
Smart Images

Figure 0007603499000004 
Figure 0007603499000005 
Figure 0007603499000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a foamable suspension-type porous vinyl chloride resin powder and a vinyl chloride plastisol composition containing the foamable suspension-type porous vinyl chloride resin powder. [Background technology]
[0002] In recent years, it has become common to use carpet tiles with sides of about 50 cm on the floors of office buildings (see, for example, Patent Document 1). This tile carpet usually has an upper pile layer in which the carpet pile is embedded, and a backing layer for maintaining strength. The backing material used for this backing layer is often a vinyl chloride resin for paste processing, which has excellent gelling properties, because it can maintain strength even under low-temperature processing conditions. In addition, this backing layer usually contains an inorganic filler such as calcium carbonate to maintain strength. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-110716 A Summary of the Invention [Problem to be solved by the invention]
[0004] As mentioned above, the backing layer of tile carpets usually contains inorganic fillers, which causes the tile carpet products to be heavy. Therefore, foaming agents have been used to make the resin layer foamed, reducing the specific gravity and making the resin layer lighter. However, when foaming agents are used, non-uniform foam cells (voids) are generated in the resin layer, and the appearance and functionality are not necessarily satisfactory.
[0005] An object of the present invention is to provide a foamable resin powder that enables fine and uniform foaming to be achieved, thereby enabling a lightweight foamed resin layer to be obtained with uniform properties, and a vinyl chloride-based plastisol composition containing the same. [Means for solving the problem]
[0006] The present inventors have found that the above problems can be solved by incorporating a thermally decomposable foaming component into the pores of a suspension-type porous polyvinyl chloride resin and using this foamable suspension-type porous polyvinyl chloride resin powder as a part of a resin layer-forming material (plastisol composition), and have completed the present invention. That is, they have found that the weight of the resin layer can be reduced by foaming the thermally decomposable foaming component during heat molding, and further that the extremely fine and uniform foaming caused by gasification of the thermally decomposable foaming component in the pores can form uniform foam cells in the resin layer, thereby obtaining a foamed resin layer with uniform properties.
[0007] That is, the present invention is as follows. [1] A foamable suspension-type porous polyvinyl chloride resin powder, characterized in that the powder contains a thermally decomposable foaming component having a decomposition temperature of 100 to 220°C within the pores of the suspension-type porous polyvinyl chloride resin powder. [2] The expandable suspension-type porous polyvinyl chloride resin powder according to [1], characterized in that the content of the thermally decomposable foaming component in the pores of the suspension-type porous polyvinyl chloride resin powder is an amount that generates 5 to 50 ml / g of thermal decomposition gas when heated at 220°C. [3] The expandable suspension-type porous polyvinyl chloride resin powder according to [1] or [2], characterized in that the content of the thermally decomposable foaming component in the pores of the suspension-type porous polyvinyl chloride resin powder is 10 volume % or more relative to the pore volume of the suspension-type porous polyvinyl chloride resin powder. [4] The expandable suspension-type porous polyvinyl chloride resin powder according to any one of [1] to [3], characterized in that the suspension-type porous polyvinyl chloride resin powder has a pore volume of 0.09 to 0.45 ml / g.
[0008] [5] A method for producing an expandable suspension-type porous polyvinyl chloride resin powder, comprising mixing a suspension-type porous polyvinyl chloride resin powder with a dispersion of a heat-decomposable foaming component having a decomposition temperature of 100 to 220°C under a heating temperature of 50°C or higher and lower than the decomposition temperature of the heat-decomposable foaming component, to produce the expandable suspension-type porous polyvinyl chloride resin powder according to any one of [1] to [4]. [6] The method for producing an expandable suspension-type porous polyvinyl chloride resin powder according to [5], characterized in that the dispersion medium of the dispersion liquid of the thermally decomposable foaming component having a decomposition temperature of 100 to 220°C is a plasticizer. [7] A vinyl chloride-based plastisol composition comprising a vinyl chloride-based resin powder for paste processing, the expandable suspension-type porous vinyl chloride-based resin powder according to any one of [1] to [4], and a plasticizer.
[0009] [8] A method for producing a vinyl chloride foam layer, comprising coating the vinyl chloride plastisol composition according to [7] above and then heating to foam the composition. [9] The method for producing a polyvinyl chloride foam layer according to [8], wherein the polyvinyl chloride foam layer is a layer constituting a tile carpet. Effect of the Invention
[0010] By using a vinyl chloride plastisol composition containing the expandable suspension-type porous vinyl chloride resin powder of the present invention, a lightweight foamed resin layer with uniform properties can be obtained. [Brief description of the drawings]
[0011] [Figure 1] 1 is a cross-sectional photograph of a foam layer produced in Example 1. [Diagram 2] 3 is a cross-sectional photograph of the foam layer produced in Example 2. [Diagram 3] 1 is a cross-sectional photograph of a foam layer produced in Example 12. [Figure 4] 3 is a cross-sectional photograph of a foamed layer produced in Comparative Example 1. [Diagram 5] 3 is a cross-sectional photograph of a foam layer produced in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] [Foamable suspension-based porous polyvinyl chloride resin powder] The expandable suspension-type porous polyvinyl chloride resin powder of the present invention is characterized in that it contains a thermally decomposable foaming component having a decomposition temperature of 100 to 220°C within the pores of the suspension-type porous polyvinyl chloride resin powder.
[0013] (Suspension-based porous polyvinyl chloride resin powder) The suspension-based porous vinyl chloride resin in the present invention is a vinyl chloride resin consisting of porous irregular particles obtained mainly by suspension polymerization, and is also called a general-purpose vinyl chloride resin. Such suspension-based porous vinyl chloride resins include homopolymers of vinyl chloride as well as copolymers mainly made of vinyl chloride. Mainly made of vinyl chloride means, for example, that vinyl chloride is 50% by mass or more of the total, preferably 70% by mass or more, and more preferably 90% by mass or more.
[0014] Examples of monomers that can be copolymerized with vinyl chloride include olefin compounds such as ethylene and propylene; vinyl esters such as vinyl acetate and vinyl propionate; unsaturated monocarboxylic acids such as acrylic acid and methacrylic acid; unsaturated monocarboxylic acid esters such as methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-hydroxyethyl acrylate, methyl methacrylate, ethyl methacrylate, and N,N-dimethylaminoethyl methacrylate; unsaturated amides such as acrylamide and methacrylamide; unsaturated nitriles such as acrylonitrile and methacrylonitrile; unsaturated dicarboxylic acids such as maleic acid and fumaric acid; esters and anhydrides thereof; N-substituted maleimides; vinyl ethers such as vinyl methyl ether and vinyl ethyl ether; and vinylidene compounds such as vinylidene chloride.
[0015] The suspension-type porous vinyl chloride resin of the present invention can be obtained by polymerizing vinyl chloride alone or a monomer mixture consisting of vinyl chloride and an unsaturated monomer copolymerizable therewith by a conventionally known method. For example, it can be obtained by suspension polymerization. By appropriately setting various reaction conditions such as temperature, type and amount of dispersant, stirring speed, etc., a resin with the desired particle size, pore volume (porosity), and polymerization degree can be obtained.
[0016] Suspension-type porous polyvinyl chloride resins are generally particles having an average particle size (D50) of about 50 to 200 μm. The average particle size (D50) is preferably 70 to 180 μm, and more preferably 100 to 150 μm. This average particle size (D50) is shown as the 50% passing diameter using a JIS Z8801 sieve according to JIS Z8815 (dry sieving test method).
[0017] The suspension-type porous vinyl chloride resin has a small specific gravity because it is porous. The pore volume of this suspension-type porous vinyl chloride resin is preferably 0.09 to 0.45 ml / g, more preferably 0.15 to 0.40 ml / g, and even more preferably 0.20 to 0.40 ml / g. By using a suspension-type porous vinyl chloride resin having a pore volume in this range as a part of a vinyl chloride plastisol composition (resin layer forming material) described later, a lightweight, homogeneous, and more well-balanced foamed resin layer can be obtained. The pore volume can be determined by mercury intrusion method (porosimeter).
[0018] The average polymerization degree of the suspension porous vinyl chloride resin is preferably 600 to 1700, more preferably 700 to 1500, and further preferably 800 to 1300. By using a suspension porous vinyl chloride resin having an average polymerization degree within this range as part of a vinyl chloride plastisol composition described below, a sol composition having good handleability and a desired viscosity can be obtained, and sufficient strength can be obtained in the formed resin layer. This average degree of polymerization is calculated by converting the reduced viscosity (K value) measured in accordance with the vinyl chloride resin testing method (published by the PVC Industry and Environment Association in April 2003) in accordance with JIS K7367-2 using the approximate formula: K value = 20.42 * Ln (degree of polymerization) - 74.93.
[0019] (Thermolyzable foaming component) The pores of the suspension-based porous polyvinyl chloride resin powder contain a thermally decomposable foaming component having a decomposition temperature of 100 to 220°C. This thermally decomposable foaming component gasifies during the heat molding of the resin layer, causing fine foaming, which enables the weight of the resin layer to be reduced. In addition, the thermally decomposable foaming component supported in the fine pores gasifies, causing very fine and uniform foaming, so that uniform foam cells are formed in the resin layer, and a foamed resin layer with uniform properties can be obtained.
[0020] The thermally decomposable foaming component used in the present invention is not particularly limited as long as it is a component that decomposes and foams at 100 to 220°C, and may be an organic foaming component or an inorganic foaming component. Examples of organic foaming components include dinitrosopentamethylenetetramine (DPT), azodicarbonamide (ADCA), p,p'-oxybisbenzenesulfonylhydrazide (OBSH), hydrazodicarbonamide (HDCA), and azobisisobutyronitrile (AIBN). Examples of inorganic foaming components include sodium hydrogen carbonate (sodium bicarbonate) and sodium borohydride. These foaming components can be used in appropriate combinations, such as organic components together, inorganic components together, or organic and inorganic components.
[0021] The decomposition temperature of the thermally decomposable foaming component may be any temperature at which the component decomposes at the heat molding temperature of the resin layer, and as described above, in the present invention, the decomposition temperature is 100 to 220°C, but preferably 120 to 210°C. In addition, since the use of a kicker component in combination with the thermally decomposable foaming component can lower the thermal decomposition temperature of the thermally decomposable foaming component and achieve foaming properties at low temperatures, it is preferable to use a kicker component in combination. Examples of the kicker component include metal oxides such as zinc oxide, magnesium oxide, and lead oxide, metal fatty acids such as zinc stearate, barium stearate, and calcium stearate contained in a heat stabilizer, and urea compounds. By appropriately combining with a kicker component, the decomposition temperature of the thermally decomposable foaming component is preferably adjusted to 120 to 180°C, more preferably 140 to 160°C.
[0022] The content of the thermally decomposable foaming component in the pores of the suspension-type porous polyvinyl chloride resin powder (per 1 g of resin) is preferably an amount that generates 5 to 50 ml / g of thermal decomposition gas when the expandable suspension-type porous polyvinyl chloride resin powder is heated to 220° C., more preferably an amount that generates 10 to 50 ml / g of thermal decomposition gas, and even more preferably an amount that generates 20 to 50 ml / g of thermal decomposition gas. By using a content that can generate gas within this range, a light, homogeneous, and more well-balanced foamed resin layer can be obtained. The amount of pyrolysis gas generated is measured by thoroughly heating the suspension-type porous polyvinyl chloride resin powder at 220° C. and measuring the amount of gas generated using a measuring device such as a gas burette.
[0023] The content of the thermally decomposable foaming component relative to the pore volume of the suspension-based porous polyvinyl chloride resin powder is preferably 10% by volume or more, more preferably 15% by volume or more, even more preferably 20% by volume or more, and particularly preferably 30% by volume or more. There is no particular upper limit to the content, and it is preferably less than 100% by volume, and more preferably 95% by volume or less. By keeping the content within this range, a light, homogeneous, and more well-balanced foamed resin layer can be obtained, as described above. The content of the thermally decomposable foaming component relative to the pore volume is calculated using the amount of the thermally decomposable foaming component introduced, the amount of the thermally decomposable foaming component present outside the pores, the pore volume of the resin powder, and the density of the thermally decomposable foaming component. Specifically, as shown in the examples.
[0024] In addition, the thermally decomposable foaming component may be partially present outside the pores, such as on the surface of the resin powder (particle), but from the viewpoint of enabling fine foaming, it is preferable that most of it is present inside the pores. For example, the thermally decomposable foaming component present outside the pores is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less of the thermally decomposable foaming component present inside the pores.
[0025] (Method for producing expandable suspension-type porous polyvinyl chloride resin powder) The expandable suspension-type porous polyvinyl chloride resin powder can be produced by mixing a suspension-type porous polyvinyl chloride resin powder with a dispersion of a thermally decomposable foaming component having a decomposition temperature of 100 to 220°C under a heating temperature of 50°C or higher and lower than the decomposition temperature of the thermally decomposable foaming component.
[0026] Considering that the foamable suspension-based porous vinyl chloride resin powder is used by blending it with a vinyl chloride-based plastisol composition for forming a resin layer, it is preferable to use a plasticizer used in the vinyl chloride-based plastisol composition as the dispersion medium. The vinyl chloride-based plastisol composition and the plasticizer will be described in detail later. In addition, organic solvents other than plasticizers may be used. Examples of organic solvents include toluene, cyclohexane, 2-methylhexane, normal heptane, cycloheptane, normal octane, 2,2,4-trimethylpentane, ethanol, 1-butanol, 2-butanol, t-butyl alcohol, 1-propanol, 2-propanol, 2-pentanol, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1,4-dioxane, ethyl acetate, butyl acetate, propyl acetate, isopropyl acetate, methyl propionate, ethyl propionate, isopropyl propionate, methyl butyrate, methyl isobutyrate, ethyl isobutyrate, 2-butanone, 2-pentanone, 3-pentanone, and 4-methyl-2-pentanone.
[0027] In the present production method, it is preferable to use a high-concentration dispersion of the thermally decomposable foaming component and heat mix it so that the thermally decomposable foaming component can easily penetrate into the pores of the suspension-type porous polyvinyl chloride resin powder and be supported therein.
[0028] The concentration of the thermally decomposable foaming component (and the kicker component) in the thermally decomposable foaming component dispersion is, for example, preferably 40 to 70 mass %, and more preferably 50 to 60 mass %.
[0029] Furthermore, as described above, the heating temperature during mixing is not particularly limited as long as it is a temperature that is 50°C or higher and lower than the decomposition temperature of the pyrolytic foaming component. However, from the viewpoint of allowing the pyrolytic foaming component to penetrate more smoothly into the pores, it is preferably 60°C or higher, and more preferably 80°C or higher.
[0030] In addition, it is preferable to use a thermally decomposable foaming component (and kicker component) having a small particle size, for example, smaller than the average pore size of the suspension-type porous polyvinyl chloride resin powder. That is, it is preferable to use a commercially available component having a small particle size so that it can easily penetrate into the pores of the expandable suspension-type porous polyvinyl chloride resin powder, or to pulverize the component before heating and mixing with the expandable suspension-type porous polyvinyl chloride resin powder.
[0031] By producing a foamable suspension-type porous polyvinyl chloride resin powder under appropriate conditions as described above, it is possible to support preferably 70 mass % or more, more preferably 75 mass % or more, even more preferably 80 mass % or more, and particularly preferably 85 mass % or more of the thermally decomposable component added within the pores.
[0032] It is also preferable to wash the expandable suspension-type porous polyvinyl chloride resin powder produced as described above with a dispersion medium (plasticizer) or the like to remove the heat-decomposable foaming component adhering to the outer surface of the powder. This allows the heat-decomposable foaming component to exist only in the pores of the resin powder, making it possible to produce finer and more uniform foams during the heat molding of the resin layer.
[0033] On the other hand, when it is used by blending it with a vinyl chloride plastisol composition for forming a resin layer, it may be used without washing from the viewpoint of production efficiency. Even if it is used without washing, by producing a foamable suspension-type porous vinyl chloride resin powder under appropriate conditions as described above, most of the thermally decomposable foaming component is supported in the pores, and a homogeneous foamed layer that can withstand practical use can be formed.
[0034] [Vinyl chloride plastisol composition] The vinyl chloride plastisol composition of the present invention is characterized by containing the vinyl chloride resin powder for paste processing, the expandable suspension-type porous vinyl chloride resin powder explained above, and a plasticizer.
[0035] The vinyl chloride plastisol composition of the present invention can form a resin layer with light weight and uniform properties. That is, by using the foamable suspension porous vinyl chloride resin of the present invention, which contains a thermally decomposable foaming component in its pores, in combination with a vinyl chloride resin for paste processing, foaming is possible by gasification of the thermally decomposable foaming component during heat molding, and the specific gravity can be reduced to achieve weight reduction. In addition, the gasification of the thermally decomposable foaming component present in the pores produces fine and uniform foaming, so that a homogeneous resin layer with uniform foam cells can be formed.
[0036] The vinyl chloride plastisol composition of the present invention preferably contains 10 to 50 mass %, more preferably 20 to 40 mass %, and even more preferably 25 to 35 mass % of the expandable suspension porous vinyl chloride resin powder. By containing the expandable suspension porous vinyl chloride resin powder in this range, the increase in viscosity can be suppressed to obtain a sol with good handleability. In addition, when a resin layer is formed, the resin layer can be sufficiently lightened and sufficient strength can be obtained.
[0037] (Powdered polyvinyl chloride resin for paste processing) The porous vinyl chloride resin for paste processing in the present invention is a vinyl chloride resin consisting of non-porous spherical fine particles obtained mainly by emulsion polymerization (including seeded emulsion polymerization) or fine suspension polymerization (including seeded fine suspension polymerization). The vinyl chloride resin powder for paste processing used in the vinyl chloride plastisol composition of the present invention may be a vinyl chloride homopolymer or a copolymer mainly composed of vinyl chloride, similar to the expandable suspension porous vinyl chloride resin powder described above.
[0038] The vinyl chloride resin powder for paste processing of the present invention can be obtained by polymerizing vinyl chloride alone or a monomer mixture consisting of vinyl chloride and an unsaturated monomer copolymerizable therewith by a conventionally known method, for example, emulsion polymerization (including seeded emulsion polymerization) or microsuspension polymerization (including seeded microsuspension polymerization).
[0039] The polyvinyl chloride resin powder for paste processing is generally fine particles having an average primary particle diameter (D50) of 0.1 to 10 μm. The average particle diameter (D50) is preferably 0.1 to 5.0 μm, and more preferably 0.5 to 3.0 μm. The average particle size (D50) refers to the particle size at the 50% point on the cumulative volume distribution curve, where the total volume of the particle size distribution determined on a volume basis is 100%, that is, the volume-based cumulative 50% diameter. The particle size distribution can be determined using a laser diffraction / scattering type particle size distribution measuring device (e.g., LA-960 manufactured by Horiba, Ltd.).
[0040] The average degree of polymerization of the polyvinyl chloride resin powder for paste processing is preferably 600 to 1700, and more preferably 900 to 1500. This average degree of polymerization is calculated in the same manner as in the case of the suspension-type porous polyvinyl chloride resin powder.
[0041] (Plasticizer) In the vinyl chloride plastisol composition of the present invention, any of the plasticizers known in the art for vinyl chloride plastisols can be used.
[0042] In the present invention, for example, phthalic acid derivatives such as dibutyl phthalate, di-(2-ethylhexyl) phthalate, di-n-octyl phthalate, diisobutyl phthalate, diheptyl phthalate, diphenyl phthalate, diisodecyl phthalate, diundecyl phthalate, butyl benzyl phthalate, dinonyl phthalate, and dicyclohexyl phthalate; isophthalic acid derivatives such as di-(2-ethylhexyl) isophthalate, diisooctyl isophthalate, and diisononyl phthalate; di-(2-ethylhexyl) tetrahydrophthalate, di-n- Tetrahydrophthalic acid derivatives such as octyl tetrahydrophthalate and diisodecyl tetrahydrophthalate; adipic acid derivatives such as di-n-butyl adipate, di-(2-ethylhexyl) adipate, diisodecyl adipate and diisononyl adipate; azelaic acid derivatives such as di-(2-ethylhexyl) azelate, diisooctyl azelate and di-n-hexyl azelate; sebacic acid derivatives such as di-n-butyl sebacate and di-(2-ethylhexyl) sebacate; di-n-butyl maleate, dimethyl maleate and diethyl maleate. maleic acid derivatives such as di-n-butyl fumarate and di-(2-ethylhexyl) fumarate; fumaric acid derivatives such as di-(2-ethylhexyl) trimellitate, tri-n-octyl trimellitate, triisodecyl trimellitate, triisooctyl trimellitate, tri-n-hexyl trimellitate, triisononyl trimellitate; pyromellitic acid derivatives such as tetra-(2-ethylhexyl) pyromellitate and tetra-n-octyl pyromellitate; triethyl citrate citric acid derivatives such as monomethyl itaconate, monobutyl itaconate, dimethyl itaconate, diethyl itaconate, dibutyl itaconate, di-(2-ethylhexyl) itaconate; oleic acid derivatives such as butyl oleate, glyceryl monooleate, diethylene glycol monooleate; ricinoleic acid derivatives such as glyceryl monoricinoleate, diethylene glycol monoricinoleate;Stearic acid derivatives such as glycerin monostearate and diethylene glycol distearate; other fatty acid derivatives such as diethylene glycol monolaurate, diethylene glycol dipelargonate, and pentaerythritol fatty acid esters; phosphoric acid derivatives such as triethyl phosphate, tributyl phosphate, tri-(2-ethylhexyl) phosphate, triphenyl phosphate, cresyl diphenyl phosphate, tricresyl phosphate, and tris(chloroethyl) phosphate; glycol derivatives such as diethylene glycol dibenzoate, dipropylene glycol dibenzoate, triethylene glycol dibenzoate, and dibutyl methylene bisthioglycolate; glycerin derivatives such as glycerol monoacetate, glycerol triacetate, and glycerol tributyrate; polyester plasticizers such as adipic acid polyesters, sebacic acid polyesters, and phthalic acid polyesters; or partially hydrogenated terphenyls and adhesive plasticizers; and further polymerizable plasticizers such as diallyl phthalate and acrylic monomers and oligomers.
[0043] Of these, the plasticizer is preferably a phthalate ester-based one. These plasticizers may be used alone or in combination of two or more. The amount of the plasticizer may be appropriately selected depending on the application, etc., but is preferably 30 to 150 parts by mass, more preferably 50 to 120 parts by mass, per 100 parts by mass of the vinyl chloride resin.
[0044] (Other Ingredients) In the vinyl chloride plastisol composition of the present invention, in addition to the vinyl chloride resin powder for paste processing, the expandable suspension-type porous vinyl chloride resin powder, and the plasticizer, various other components may be blended in. Examples of the other components include a heat stabilizer, a filler, a foaming agent, a foaming accelerator, a viscosity regulator, an adhesion imparting agent, a colorant, a diluent, an ultraviolet absorber, an antioxidant, and a reinforcing agent.
[0045] The vinyl chloride plastisol composition of the present invention is a sol with a relatively low viscosity, and the optimum viscosity varies depending on the molding method, but from the viewpoints of handling and adhesiveness, it is preferably 2000 to 13000 mPa s, and more preferably 3000 to 12000 mPa s. This viscosity is measured by the measurement method shown in the examples.
[0046] [Method of producing vinyl chloride plastisol composition] The vinyl chloride plastisol composition of the present invention can be produced by mixing the vinyl chloride resin powder for paste processing, the expandable suspension porous vinyl chloride resin powder, and the plasticizer, and other components as necessary. The vinyl chloride resin for paste processing, the expandable suspension porous vinyl chloride resin, and the plasticizer can be mixed in any order. That is, the three components may be mixed simultaneously, or two components may be mixed and then the remaining component may be mixed.
[0047] [Method of manufacturing vinyl chloride foam layer] The method for producing a vinyl chloride foam layer of the present invention is characterized in that the vinyl chloride plastisol composition of the present invention is applied to a substrate or the like, and then heated to foam. In the production method of the present invention, fine bubbles are generated during heating and foaming, so that the foam layer produced becomes a light and homogeneous layer. The heating temperature is not particularly limited as long as the vinyl chloride plastisol composition of the present invention melts and the thermally decomposable foaming component decomposes at the same time, but is, for example, 120 to 250°C, preferably 150 to 200°C.
[0048] Specifically, suitable examples of the vinyl chloride foam layer include layers constituting tile carpets, such as the backing layer and adhesive layer of tile carpets, etc. Other examples include layers constituting wall materials, floor materials, and leather. EXAMPLES
[0049] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0050] [Example 1] <Production of Expandable Suspension-Type Porous Polyvinyl Chloride Resin Powder> 80 g of di-(2-ethylhexyl)phthalate (DOP, manufactured by J-Plus Corporation) as a dispersion medium, 20 g of a Ba-Zn stabilizer (BZ-100CJ, manufactured by Katsuta Chemical Industry Co., Ltd.) as a kicker component, and 80 g of a foaming agent (ADCA, Vinihol AC#3-K2, manufactured by Eiwa Chemical Industry Co., Ltd.) as a thermally decomposable foaming component were placed in a mortar and mixed while grinding the foaming agent in a mortar for 30 minutes to prepare a foaming agent dispersion.
[0051] Then, a suspension-type porous polyvinyl chloride resin powder (ZEST 1700ZI (Shin-Daiichi Vinyl Corporation), internal pore volume 0.37 cm) was added to a 2 L Henschel mixer (Mitsui Miike Manufacturing Co., Ltd.). 3 After adding 400 g of ethanol (1 / g), the entire amount of the foaming agent dispersion prepared above was added while stirring at a rotation speed of 1000 rpm, the jacket was heated to 90° C., and then it was cooled to room temperature.
[0052] In order to remove the foaming agent present on the outside (external surface, etc.) of the internal pores of the foamable suspension-type porous polyvinyl chloride resin powder produced above, 100g of DOP was added to 100g of the foamable suspension-type porous polyvinyl chloride resin, and filtered through a 500 mesh (opening diameter 25μm) wire net.Furthermore, by subjecting it to a centrifuge at 1000rpm for 2 minutes, a foamable suspension-type porous polyvinyl chloride resin powder with the foaming agent supported in the internal pores was obtained.
[0053] <Production of vinyl chloride plastisol composition> A 1-L plastic cup was charged with 70 g of polyvinyl chloride resin for paste processing (ZEST PQ135 (Shin-Daiichi Vinyl Co., Ltd.)), 45 g of the foamable suspension-type porous polyvinyl chloride resin powder produced above (containing 30 g of ZEST 1700ZI), 142 g of DOP (total amount including DOP in the foamable suspension-type porous polyvinyl chloride resin powder was 150 g), 2 g of Ba-Zn-based stabilizer (BZ-100CJ, Katsuta Chemical Co., Ltd.), and 300 g of calcium carbonate (Kansui #70, Nitto Funka Kogyo Co., Ltd.) and stirred at 600 rpm for 10 minutes using a mechanically controlled stirrer to produce a polyvinyl chloride-based plastisol composition.
[0054] <Production of polyvinyl chloride foam layer> The vinyl chloride plastisol composition was coated onto a stainless steel plate (thickness 0.8 mm) with a doctor blade to a thickness of 1 mm, and immediately heated in a Geer oven at 200° C. for 5 minutes to obtain a foam layer (foam-molded sheet).
[0055] [Example 2] The same procedure as in Example 1 was repeated, except that the amount of foaming agent used when supporting the foaming agent in the internal pores of the suspension-type porous polyvinyl chloride resin powder was changed to 140 g.
[0056] [Example 3] The same procedure as in Example 1 was repeated, except that the jacket heating condition for supporting the blowing agent in the internal pores of the suspension-type porous polyvinyl chloride resin powder was changed to 60°C.
[0057] [Example 4] The same procedure as in Example 1 was repeated, except that the jacket heating condition for supporting the blowing agent in the internal pores of the suspension-type porous polyvinyl chloride resin powder was changed to 30°C.
[0058] [Example 5] The same procedure as in Example 1 was repeated, except that the plasticizer used to support the blowing agent in the internal pores of the suspension-type porous polyvinyl chloride resin powder was changed to diisononyl phthalate (DINP).
[0059] [Example 6] The same procedure as in Example 1 was repeated, except that the plasticizer used to support the blowing agent in the internal pores of the suspension-type porous polyvinyl chloride resin powder was changed to di-(2-ethylhexyl) adipate (DOA).
[0060] [Example 7] The same procedure as in Example 1 was repeated, except that the blowing agent supported in the internal pores of the suspension-type porous polyvinyl chloride resin powder was changed to p,p'-oxybisbenzenesulfonylhydrazide (OBSH).
[0061] [Example 8] In Example 1, the suspension-type porous polyvinyl chloride resin powder (ZEST 1700ZI) carrying the blowing agent was replaced with ZEST 1000Z (Shin-Daiichi Vinyl Corporation, internal pore volume 0.27 cm 3 The procedure of Example 1 was repeated except that the concentration of 100 mg / g was changed to 100 mg / g.
[0062] [Example 9] The same procedure as in Example 1 was repeated, except that the dispersion medium used for supporting the blowing agent in the internal pores of the suspension-type porous polyvinyl chloride resin powder was changed to toluene (an organic solvent).
[0063] [Example 10] Example 1 was repeated, except that the amount of foaming agent used to support the foaming agent in the internal pores of the suspension-type porous polyvinyl chloride resin powder was changed to 10 g.
[0064] [Example 11] In Example 1, the suspension-type porous polyvinyl chloride resin powder (ZEST 1700ZI) carrying the blowing agent was replaced with ZEST 700L (Shin-Daiichi Vinyl Corporation, internal pore volume 0.09 cm 3 The procedure of Example 1 was repeated except that the concentration of 100 mg / g was changed to 100 mg / g.
[0065] [Example 12] Example 2 was carried out in the same manner as in Example 2, except that the treatment for removing the blowing agent present outside the internal pores of the suspension-type porous polyvinyl chloride resin powder carrying the blowing agent was not carried out.
[0066] [Comparative Example 1] Example 1 was carried out in the same manner as in Example 1, except that no foaming agent was supported in the internal pores of the suspension-type porous polyvinyl chloride resin powder, and when producing the polyvinyl chloride plastisol, 100 g of polyvinyl chloride resin powder for paste, 150 g of DOP, 5.4 g of ADCA, 3.5 g of Ba-Zn-type stabilizer, and 300 g of calcium carbonate were added and stirred for 10 minutes at 600 rpm using a mechanically controlled stirrer to produce a polyvinyl chloride plastisol composition.
[0067] [Comparative Example 2] In Example 1, a foaming agent was not supported in the internal pores of the suspension-type porous polyvinyl chloride resin powder, and when producing the polyvinyl chloride plastisol, 70 g of polyvinyl chloride resin for paste, 30 g of suspension-type porous polyvinyl chloride resin, 150 g of DOP, 5.4 g of ADCA, 3.5 g of Ba-Zn-type stabilizer, and 300 g of calcium carbonate were added and stirred at 600 rpm for 10 minutes using a mechanically controlled stirrer to produce a polyvinyl chloride plastisol composition. The procedure was the same as in Example 1, except that a foaming agent was not supported in the internal pores of the suspension-type porous polyvinyl chloride resin powder, and a vinyl chloride plastisol composition was produced by adding 70 g of polyvinyl chloride resin for paste, 30 g of suspension-type porous polyvinyl chloride resin, 150 g of DOP, 5.4 g of ADCA, 3.5 g of Ba-Zn-type stabilizer, and 300 g of calcium carbonate.
[0068] The expandable suspension-type porous polyvinyl chloride resin powders, polyvinyl chloride plastisol compositions, and polyvinyl chloride foamed layers (foam-molded sheets) according to the above Examples 1 to 12 and Comparative Examples 1 and 2 were subjected to the following measurements and evaluations.
[0069] (Pore volume of foamable suspension-type porous polyvinyl chloride resin powder) The measurements were performed using a mercury intrusion porosimeter.
[0070] (Amount of gas generated by pyrolysis of foamable suspension-type porous polyvinyl chloride resin powder) 10 g of foamable suspension-type porous polyvinyl chloride resin powder with a foaming agent supported in the internal pores was placed in a three-neck flask, and then 30 g of liquid paraffin was added and heated to 220°C in an oil bath. After heating at 220°C for 20 minutes, the amount of gas generated was measured using a gas burette.
[0071] (Blowing agent content relative to pore volume of suspension-type porous polyvinyl chloride resin powder (volume fraction φ)) The volume fraction φ was calculated from the following formula.
[0072] Volume fraction φ(%)=(mb-ma) / ρ / v
[0073] In the formula, "ma" is the mass (g) of the thermally decomposable foaming component outside the pores recovered by the centrifugation process, "mb" is the theoretical value (g) of the thermally decomposable foaming component contained in 100 g of the blowing agent-supported suspension-type porous polyvinyl chloride resin powder (amount added per 100 g of resin powder), and "v" is the pore volume (cm) per 1 g of the suspension-type porous polyvinyl chloride resin powder. 3 / g), and "ρ" is the density of the pyrolyzable foaming component (g / cm 3 ) (ρ = 1.50 for both ADCA and OBSH).
[0074] (Viscosity of Vinyl Chloride Plastisol Composition) The plastisol composition was allowed to stand for 1 hour in an atmosphere with a temperature of 23° C. and a humidity of 50% RH, and then thoroughly mixed, and the viscosity was measured using a Brookfield viscometer (LVDV-3T manufactured by Eiko Seiki Co., Ltd.) with rotor No. 4 at 60 rpm.
[0075] (Expansion ratio of foam layer) The center of the foam-molded sheet was punched out with a 4 cm square die, and the cross section of the foam-molded sheet was observed enlarged with a CCD camera, and the average value of the distance between two points in the thickness direction was recorded as the thickness L. The thickness of the coating layer (before foaming) was regarded as the thickness L0 obtained by the above measurement method for the molded sheet obtained by heating for 5 minutes in an oven with an internal temperature of 140°C, and the foaming ratio was calculated as L / L0.
[0076] (Specific gravity of foam layer) From the foam molding sheet 4cm square (16cm 2 The mass was measured using a precision balance. The volume was calculated by multiplying the thickness calculated in the measurement of the expansion ratio by the surface area, and the specific gravity was calculated by dividing the mass by the volume.
[0077] (Tensile strength of foam layer) The tensile strength was measured by preparing dumbbell-shaped tensile test pieces from the foam-molded sheets and measuring the tensile strength with an autograph (AGS-H, manufactured by Shimadzu Corporation). The tensile strength test samples used were No. 2 type test pieces, and the test was performed at a test speed of 200 mm, with the average value of n=5 being calculated.
[0078] (Cross-section evaluation of foam layer) The cross section of the foam layer (foam-molded sheet) was observed at 50x magnification with a CCD camera, and the denseness of the foam layer was evaluated according to the following criteria.
[0079] ⊚: Extremely dense and uniform foam cells. ◯: Has fairly dense and uniform foam cells. Δ: Somewhat coarse or non-uniform foam cells are present. ×: Coarse foam cells are present.
[0080] The results are shown in Tables 1 to 3. Moreover, cross-sectional photographs of the foamed layers of Examples 1, 2 and 12 and Comparative Examples 1 and 2 are shown in Figs.
[0081] [Table 1]
[0082] [Table 2]
[0083] [Table 3]
[0084] As shown in Tables 1-2 and Figures 1-3, by using the vinyl chloride plastisol compositions of Examples 1-12, a foam layer having a high expansion ratio and a low specific gravity was produced, and dense and uniform foam cells were formed in the produced foam layer, and the foam layer had uniform properties. In addition, the tensile strength was also sufficiently high. Furthermore, the viscosity of the plastisol composition was low, making it easy to handle.
[0085] The amount of pyrolysis gas generated by the resin powder of Example 2 was 43.1 ml / g, and the amount of pyrolysis gas generated by the resin powder of Example 12 was 54.3 ml / g. From these results, it can be seen that the amount of pyrolysis foaming component present on the outside (outer surface) of the internal pores of the resin powder in Example 12 was 26.0% of the amount of pyrolysis foaming component supported in the internal pores. Example 12, in which the pyrolysis foaming component was present on the resin powder surface, had inferior foam cell properties compared to Example 2, but was sufficiently practical.
[0086] On the other hand, as shown in Table 3 and Figures 4 to 5, when a heat-decomposable foaming component was added to the plastisol composition without using a suspension-based porous polyvinyl chloride resin powder as in Comparative Example 1, or when a foaming component was not contained in the suspension-based porous polyvinyl chloride resin powder but a heat-decomposable foaming component was added to the plastisol composition as in Comparative Example 2, coarse and non-uniform foam cells were formed in the produced foam layer. [Industrial Applicability]
[0087] INDUSTRIAL APPLICABILITY The vinyl chloride plastisol composition of the present invention is industrially useful since it can be used for forming a backing layer of a tile carpet, etc.
Claims
1. A suspension-type porous polyvinyl chloride resin powder having an average particle size (D50) of 50 to 150 μm contains a thermally decomposable foaming component having a decomposition temperature of 100 to 220° C. in the pores thereof, The content of the thermally decomposable foaming component in the pores of the suspension-type porous polyvinyl chloride resin powder is an amount that generates 20 to 50 ml / g of thermal decomposition gas when heated at 220°C.
1. A foamable suspension-type porous polyvinyl chloride resin powder comprising:
2. 2. The expandable suspension-type porous polyvinyl chloride resin powder according to claim 1, characterized in that the content of the thermally decomposable foaming component in the pores of the suspension-type porous polyvinyl chloride resin powder is 10 volume % or more relative to the pore volume of the suspension-type porous polyvinyl chloride resin powder.
3. 3. The expandable suspension-type porous polyvinyl chloride resin powder according to claim 1, characterized in that the pore volume of the suspension-type porous polyvinyl chloride resin powder is 0.09 to 0.45 ml / g.
4. A method for producing an expandable suspension-type porous polyvinyl chloride resin powder, comprising mixing a suspension-type porous polyvinyl chloride resin powder with a dispersion of a heat-decomposable foaming component having a decomposition temperature of 100 to 220°C under a heating temperature of 50°C or higher and lower than the decomposition temperature of the heat-decomposable foaming component, to produce the expandable suspension-type porous polyvinyl chloride resin powder according to any one of claims 1 to 3.
5. The method for producing the expandable suspension-type porous polyvinyl chloride resin powder according to claim 4, characterized in that the dispersion medium of the dispersion liquid of the thermally decomposable foaming component having a decomposition temperature of 100 to 220°C is a plasticizer.
6. A vinyl chloride-based plastisol composition comprising a vinyl chloride-based resin powder for paste processing, the expandable suspension-type porous vinyl chloride-based resin powder according to any one of claims 1 to 3, and a plasticizer.
7. A method for producing a vinyl chloride foamed layer, which comprises coating the vinyl chloride plastisol composition according to claim 6 and then heating to foam it.
8. 8. The method for producing a vinyl chloride foamed layer according to claim 7, wherein the vinyl chloride foamed layer is a layer constituting a tile carpet.
Citation Information
Patent Citations
JP1973056268A
Mat made of synthetic resin foam
JP2005042416A
Tile carpet
JP2009261631A
Tile carpet and manufacturing method of the same
JP2018110716A
Foamable vinyl chloride-based resin paste and vinyl chloride-based resin foamed sheet using the same
JP2018131594A
